Identification of insulin-mimetic phytochemicals from mas cotek (Ficus deltoidea) for treatment of type 2 diabetes via LC-MS/MS and molecular docking analyses - Eng, Shu Man; Mohd Ezuan, Khayat (Hibiscus Publisher, 2023)
Type 2 diabetes mellitus, a metabolic syndrome, has become increasingly prevalent in recent years. In the treatment of chronic T2DM, patients are required to take insulin daily, commonly through injections, as the hormone can easily be degraded by the digestive system if taken orally. This can be an uncomfortable experience for the patient. Thus, finding an alternative to insulin, especially from natural compounds, would be beneficial. Ficus deltoidea, which belongs to the Moraceae family, is a medicinal plant known for its anti-diabetic properties. Therefore, this study aimed to identify the phytochemicals from F. deltoidea that mimic insulin by studying their ability to bind to insulin receptors using in silico analysis. A total of 36 phytochemicals were identified in the methanolic extract of F. deltoidea through LC-MS/MS analysis. They were then subjected to molecular docking to determine their binding free energy with the insulin receptor (IR). The results revealed seven phytochemicals with the lowest binding free energy, with 2,3-dihydroxy-N,N'-bis[(E)-1-(4-hydroxy-6-methyl-2-oxochromen-3-yl)ethylideneamino] butanediamide exhibiting the lowest binding free energy at -10.0 kcal/mol. Hence, these phytochemicals demonstrate potential as insulin-mimetic compounds that can be used in the treatment of T2DM.